Conversion of Escherichia coli into Mixotrophic CO2 Assimilation with Malate and Hydrogen Based on Recombinant Expression of 2-Oxoglutarate:Ferredoxin Oxidoreductase Using Adaptive Laboratory Evolution - Yu-Chen Cheng; Wei-Han Huang; Shou-Chen Lo; Eugene Huang; En-Pei Isabel Chiang; Chieh-Chen Huang; Ya-Tang Yang (Microorganisms, 2023)
We report the mixotrophic growth of Escherichia coli based on recombinant 2-oxoglutarate:ferredoxin oxidoreductase (OGOR) to assimilate CO2 using malate as an auxiliary carbon source and hydrogen as an energy source. We employ a long-term (~184 days) two-stage adaptive evolution to convert heterotrophic E. coli into mixotrophic E. coli. In the first stage of evolution with serine, diauxic growth emerges as a prominent feature. At the end of the second stage of evolution with malate, the strain exhibits mixotrophy with CO2 as an essential substrate for growth. We expect this work will open new possibilities in the utilization of OGOR for microbial CO2 assimilation and future hydrogen-based electro-microbial conversion.